Intra-Extracardiac Versus Extracardiac Fontan Modifications: Comparison of Early Outcomes - (:unkn) unknown (ELSEVIER SCIENCE INC, 2019)
Background. The intra-extracardiac (IE) Fontan modification has advantages over the lateral tunnel modification. A direct comparison of IE to the extracardiac (EC) modification so far has not been done. This study compared IE to EC Fontan with respect to early post-operative outcomes. Methods. We retrospectively compared outcomes of the Fontan operation using the IE or EC conduit modification between January 2012 and December 2016. IE and EC groups were compared using univariate and multivariable regression analysis. To eliminate the confounding effects of fenestration, repeat intergroup comparison was performed after excluding non-fenestrated patients. Results. There were 81 patients grouped according to Fontan modification into the IE group (n = 43) or EC group (n = 38). The Fontan was fenestrated in 100% of the IE group but in only 55% of the EC group (p < 0.001). Cardiopulmonary bypass time was shorter for the IE group (74 vs 103, p < 0.001) The IE patients had median cross-clamp time of 34 minutes, whereas only 2 patients in the EC group required cross-clamping (35 and 95 minutes; p < 0.001). The IE group had significantly shorter median duration of pleural effusion (8 days vs 11 days, p = 0.007) and hospital length of stay (9 days vs 13 days, p = 0.001) than the EC group. Multivariable linear regression analysis revealed that the IE modification was independently associated with reduced duration of pleural effusion (p = 0.004) and hospital length of stay (p = 0.003). Presence of any unfavorable hemodynamics on preoperative assessment was also associated with longer duration of pleural effusion and hospital length of stay for patients with fenestration. Conclusions. The IE Fontan modification may be associated with reduced duration of postoperative pleural effusion and hospital length of stay compared with the EC modification. (C) 2019 by The Society of Thoracic Surgeons
Keywords: FENESTRATION; REPAIR